Quality improvement in emergency obstetric referrals: qualitative study of provider perspectives in Assin North district, Ghana - Afari, Henrietta (BMJ Publishing Group, 2014)
OBJECTIVE: To describe healthcare worker (HCW)-identified system-based bottlenecks and the value of local engagement in designing strategies to improve referral processes related to emergency obstetric care in rural Ghana. DESIGN: Qualitative study using semistructured interviews of participants to obtain provider narratives. SETTING: Referral systems in obstetrics in Assin North Municipal Assembly, a rural district in Ghana. This included one district hospital, six health centres and four local health posts. This work was embedded in an ongoing quality improvement project in the district addressing barriers to existing referral protocols to lessen delays. PARTICIPANTS: 18 HCWs (8 midwives, 4 community health officers, 3 medical assistants, 2 emergency room nurses, 1 doctor) at different facility levels within the district. RESULTS: We identified important gaps in referral processes in Assin North, with the most commonly noted including recognising danger signs, alerting receiving units, accompanying critically ill patients, documenting referral cases and giving and obtaining feedback on referred cases. Main root causes identified by providers were in four domains: (1) transportation, (2) communication, (3) clinical skills and management and (4) standards of care and monitoring, and suggested interventions that target these barriers. Mapping these challenges allowed for better understanding of next steps for developing comprehensive, evidence-based solutions to identified referral gaps within the district. CONCLUSIONS: Providers are an important source of information on local referral delays and in the development of approaches to improvement responsive to these gaps. Better engagement of HCWs can help to identify and evaluate high-impact holistic interventions to address faulty referral systems which result in poor maternal outcomes in resource-poor settings. These perspectives need to be integrated with patient and community perspectives.